REVITALISING THE RESTAURANT INDUSTRY OF PAKISTAN AMIDST COVID-19 PANDEMIC: THE LINKAGE BETWEEN PARAMOUNT FUNDAMENTALS - Sohail, Farhan; Abbas, Mehdi; Qasim, Sehrish; Khan, Essa; Siddiqui, Arsalan Ahmed; Ali, Syed Rizwan (The journal of contemporary issues in business and government, 2022)
Due to the ongoing pandemic it has been decided by the authorities in major cities of Pakistan to impose new restrictions to indoor dining following a rise in coronavirus cases. The present study revolves around open-air restaurants' traits in COVID 19 in Pakistan connected with consumer perception related to their health awareness and hygiene quality. It also looks at one of the toughest challenges in the pandemic for open-air restaurants i.e. to follow the COVID 19 protocols while maintaining top-notch quality in food service and quality. Also, the customers' re-experience intention to a more considerable extent with respect to the restaurant's hygiene trust has also been discussed. The study finds the relationship between COVID-19 protocols, food quality, service quality, hygiene trust, satisfaction and re-experiencing the same place. For this purpose, the data have been collected from 10 open air restaurants in Pakistan via survey. The results revealed that there lies a strong linkage between the above mentioned variables during the pandemic.